Outcome Reporting Bias in Randomized Experiments on Substance Use Disorders - Wooditch, Alese (Journal of quantitative criminology, 2020)
This cohort study explores the prevalence and effect of suspected outcome reporting bias in clinical trials on substance use disorders.